2020
DOI: 10.7554/elife.61171
|View full text |Cite
|
Sign up to set email alerts
|

SMC5/6 is required for replication fork stability and faithful chromosome segregation during neurogenesis

Abstract: Mutations of SMC5/6 components cause developmental defects, including primary microcephaly. To model neurodevelopmental defects, we engineered a mouse wherein Smc5 is conditionally knocked out (cKO) in the developing neocortex. Smc5 cKO mice exhibited neurodevelopmental defects due to neural progenitor cell (NPC) apoptosis, which led to reduction in cortical layer neurons. Smc5 cKO NPCs formed DNA bridges during mitosis and underwent chromosome missegregation. SMC5/6 depletion triggers a CHEK2-p53 DNA damage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 144 publications
7
26
1
Order By: Relevance
“…To investigate the two principal underlying causes of microcephaly, slowed cell cycle progression and/or increased apoptosis in the developing brain 2 , 26 28 , fixed whole-mount slf2 and smc5 depleted zebrafish embryos were stained with markers of cell cycle stage (G2/M: phospho-histone H3 serine-10) and apoptosis (TUNEL). F0 CRISPR embryos injected with either slf2 or smc5 sgRNA with recombinant Cas9 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the two principal underlying causes of microcephaly, slowed cell cycle progression and/or increased apoptosis in the developing brain 2 , 26 28 , fixed whole-mount slf2 and smc5 depleted zebrafish embryos were stained with markers of cell cycle stage (G2/M: phospho-histone H3 serine-10) and apoptosis (TUNEL). F0 CRISPR embryos injected with either slf2 or smc5 sgRNA with recombinant Cas9 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, activation of the MSP is only one of several possible pathways that can result in reduced cortical size. In fact, it was shown that microcephaly caused by loss of SMC5 in the brains of mice is independent of the MSP and thus cannot be rescued by knocking out the MSP signaling components 53BP1 and USP28 ( Atkins et al 2020 ; Phan et al 2021 ). However, this same microcephaly model can be rescued by knocking out CHK2 or P53, indicating that DNA damage signaling is predominantly responsible for the impaired cortical growth in these animals ( Atkins et al 2020 ).…”
Section: Perspectivementioning
confidence: 99%
“…In fact, it was shown that microcephaly caused by loss of SMC5 in the brains of mice is independent of the MSP and thus cannot be rescued by knocking out the MSP signaling components 53BP1 and USP28 ( Atkins et al 2020 ; Phan et al 2021 ). However, this same microcephaly model can be rescued by knocking out CHK2 or P53, indicating that DNA damage signaling is predominantly responsible for the impaired cortical growth in these animals ( Atkins et al 2020 ). Identifying which microcephaly mutations activate the MSP and which trigger other pathogenic pathways is an important area of future research.…”
Section: Perspectivementioning
confidence: 99%
“…It evades the irreversibility of gene knockout strategies, and is not hindered by incomplete silencing and off-target effects ( Jackson et al, 2003 ; Kaelin, 2012 ). In addition, the AID system provides a powerful research tool for studying highly dynamic biological processes, such as the cell cycle, stem cell differentiation and neural activity ( Nora et al, 2017 ; Ng et al, 2019 ; Atkins et al, 2020 ). Unlike other gene silencing strategies, AID-mediated degradation rapid depletion of proteins of interest (POI) within minute or hourly timescales can directly attribute the observed phenotypes to POI function rather than secondary effects arising from the actions of indirect targets ( Weiss et al, 2007 ; Wood et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%